Cervical vestibular evoked myogenic potentials in healthy children: Normative values for bone and air conduction - Wiener-Vacher, Sylvette R.; Campi, Marta; Boizeau, Priscilla; Thai-Van, Hung (Frontiers in Neurology, 2023)
Objectives To characterize cervical vestibular evoked myogenic potentials (c-VEMPs) in bone conduction (BC) and air conduction (AC) in healthy children, to compare the responses to adults and to provide normative values according to age and sex. Design Observational study in a large cohort of healthy children (n = 118) and adults (n = 41). The c-VEMPs were normalized with the individual EMG traces, the amplitude ratios were modeled with the Royston-Wright method. Results In children, the amplitude ratios of AC and BC c-VEMP were correlated (r = 0.6, p < 0.001) and their medians were not significantly different (p = 0.05). The amplitude ratio was higher in men than in women for AC (p = 0.04) and BC (p = 0.03). Children had significantly higher amplitude ratios than adults for AC (p = 0.01) and BC (p < 0.001). Normative values for children are shown. Amplitude ratio is age-dependent for AC more than for BC. Confidence limits of interaural amplitude ratio asymmetries were less than 32%. Thresholds were not different between AC and BC (88 ± 5 and 86 ± 6 dB nHL, p = 0.99). Mean latencies for AC and BC were for P-wave 13.0 and 13.2 msec and for N-wave 19.3 and 19.4 msec. Conclusion The present study provides age- and sex-specific normative data for c-VEMP for children (6 months to 15 years of age) for AC and BC stimulation. Up to the age of 15 years, c-VEMP responses can be obtained equally well with both stimulation modes. Thus, BC represents a valid alternative for vestibular otolith testing, especially in case of air conduction disorders.